Performance Optimization of Nozzle-Diffuser Piezoelectric Micropump with Multiple Vibrating Membranes by Design of Experiment (DOE) Method - S. Bayazidi; M. Mojaddam; A. Mohseni (Journal of Applied Fluid Mechanics, 2023)
During recent years, microfluidics based microelectromechanical systems (MEMSs) have found multiple applications in biomedical engineering. One of their most important implementations is fluid transfer in microliter and nanoliter scales. Nowadays, micropumps are extensively used in various medical applications such as drug delivery. In this study, the performance of a piezoelectric micropump is investigated and optimized. This micropump consists of a pump chamber and three deformable walls in a nozzle-diffuser shape, which are used to create pressure gradient between the inlet and outlet. The performance of the micropump is evaluated by transient Computational Fluid Dynamics (CFD) simulation using dynamic mesh. Then its performance is optimized using the Design of Experiment (DOE) method based on mean net outlet mass flow rate and flow reversibility at the pump outlet. The results indicate an improvement of 34.5% in mean net outlet mass flow rate and a significant decrease in reversibility. The maximum mean net outlet mass flow rate and the minimum reversibility corresponding to the optimum geometries are 95.82 mL/min and 0.05%, respectively.